Indonesia Economic Quarterly, December 2014 : Delivering Change - World Bank (Washington, DC, 2015)
The Indonesia Economic Quarterly (IEQ) has two main aims. First, it reports on the key developments over the past three months in Indonesia s economy, and places these in a longerterm and global context. Based on these developments, and on policy changes over the period, the IEQ regularly updates the outlook for Indonesia s economy and social welfare. Second, the IEQ provides a more in-depth examination of selected economic and policy issues, and analysis of Indonesia s medium-term development challenges. It is intended for a wide audience, including policymakers, business leaders, financial market participants, and the community of analysts and professionals engaged in Indonesia s evolving economy.